Flatwise compression and local indentation response of 3D-printed strut-reinforced Kagome with polyurethane filling - Gautam, Rinoj (2022)
Additively manufactured lattice structures are finding wider applications as core materials because of their high specific strength, modulus, and energy absorption. Strut-reinforced Kagome (SRK) structures have been shown to have good compressive performance compared with many existing lattice structures.Herein, the performance of acrylonitrile butadiene styrene (ABS) SRK lattice structures fabricated by fused deposition modeling under flatwise compression and local loading was investigated with and without polyurethane foam fillers. The SRK structure demonstrated abrupt failure at the joints in the vicinity of the face sheet, thereby reducing the energy absorption of the structure. The SRK filled with low-density polyurethane foam had no significant effect on peak failure load and moduli, whereas energy absorption per unit mass was higher by 16.5%.The SRK filled with high-density foam showed 116% increase in energy absorption. Similarly, a stronger indentation response was observed with high-density foam-filled SRK sandwich structures.